2015
DOI: 10.5433/1679-0359.2015v36n6p3579
|View full text |Cite
|
Sign up to set email alerts
|

Sources and application methods of boron in Eucalyptus crop

Abstract: Cerrado soils have low boron (B) content, making supplementation of this element through fertilization via soil and/or leaf is a common practice. It is therefore important to establish the best mode of application and source of B for the proper development of eucalyptus. Thus, the objective of this study was to compare the effect of B sources with high and low solubility on eucalyptus cultivation and to examine the effect of foliar application of the micronutrient. The experiment was conducted in an area locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…A similar result was observed by Celestrino et al (2015) in Eucalyptus urophylla, which 24 months after planting presented an increase in B concentration in the leaves in response to foliar application, however, there was no improvement in growth, diameter or volume of wood.…”
Section: (** = Significant P-value At 1% By the F-test)supporting
confidence: 68%
“…A similar result was observed by Celestrino et al (2015) in Eucalyptus urophylla, which 24 months after planting presented an increase in B concentration in the leaves in response to foliar application, however, there was no improvement in growth, diameter or volume of wood.…”
Section: (** = Significant P-value At 1% By the F-test)supporting
confidence: 68%
“…Under the same soil and climatic conditions, in the first cycle of Eucalyptus, Gazola et al [29] verified that the maximum yield of Eucalyptus was obtained at 21 months of age with the application of 71 kg ha −1 of N, 100 kg ha −1 of P 2 O 5 , and 125 kg ha −1 of K 2 O. Celestrino [33] observed positive results for plant height, DBH, and VW with a dose of 1 kg ha −1 of B applied to the Eucalyptus.…”
Section: Concentrations Of N and P In The Leaves And In The Littermentioning
confidence: 99%
“…Foliar B applications reduced the percentage of tree forks until 42 months after planting (Table 7); however, there was no interaction between soil and foliar application, according to results obtained by Celestrino et al (2015) at 24 months after planting. The authors also observed that even with the omission of B at planting, foliar applications (total of 0.425 kg ha -1 of B) were sufficient to reduce 35% of tree forks, when compared to the control group.…”
Section: ( )mentioning
confidence: 74%